PROTECTION OF THIRD PARTY PERSONAL DATA WHEN USING EMERGENCY CONTACTS ON THE SHOPEE PAYLATER SERVICE - Elmo Septian Rasyid; Ainun Nabilah; Cahya Utami Aldana; Miranti Dwi Pangesti; Andriyanto Adhi Nugroho (Journal of Governance and Law Reform, 2026)
This research examines the protection of third-party personal data in the practice of providing emergency contact information within Buy Now Pay Later services, particularly Shopee PayLater, where such data is often included without the consent of its actual owner. This situation raises significant legal concerns because third parties, who have no contractual relationship with the service provider, nonetheless become subjects of data processing and debt collection activities. The study employs a normative juridical method by analyzing the Personal Data Protection Law, the Electronic Information and Transactions Law, Government Regulation Number 71 of 2019, sectoral regulations issued by the Financial Services Authority, and relevant judicial decisions including the Central Jakarta District Court Decision Number 689 Pdt G 2021 and the Supreme Court Decision Number 1206 K Pdt 2024. Using the right to privacy theory and consent theory, the findings show that processing third-party data without direct and explicit consent contradicts fundamental principles of personal data protection and violates individual privacy rights. The research further reveals that Indonesia’s current legal framework does not provide a comprehensive mechanism for third-party consent, resulting in regulatory gaps related to data collection, consent verification, and limitations on the use of third-party information in digital financial services. This study concludes that existing regulations do not provide adequate protection for third parties and highlights the need for more detailed legal provisions governing the collection, verification, and restricted use of emergency contact data within Buy Now Pay Later services.